2000
DOI: 10.1002/(sici)1096-9837(200003)25:3<329::aid-esp83>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

SHORT COMMUNICATION��A field experiment of cusp formation on a coarse clastic beach using a suspended video-camera system

Abstract: Cusp formation was continuously monitored on a manually flattened, plane section of a coarse clastic, microtidal, pocket beach on the Pacific coast of Japan using a CCD camera suspended in the air. Vertical video pictures enabled the examination of the temporal change in foreshore morphologies and swash pattern. Boulders on the beach face appeared to have triggered the formation of beach cusps, which gradually and successively grew up alongshore. In 2Á5 h, two well defined beach cusps had developed with a spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…This hypothesis, which is impossible to test, reduces the role of the forcing template to a source of perturbation upon which the instability operates just like the presence of a non-erodable structure (Sunamura and Aoki, 2000), sandcastles, or any other source of variation from a planar slope . Overall, the Werner and Fink (1993) model remains a landmark study because it introduced the idea of selforganization to explain the occurrence of morphological patterns, emphasized the role of morphodynamics, and paved the way to many new studies on the role of selforganization in the nearshore.…”
Section: Discussion Of Beach Cuspsmentioning
confidence: 99%
“…This hypothesis, which is impossible to test, reduces the role of the forcing template to a source of perturbation upon which the instability operates just like the presence of a non-erodable structure (Sunamura and Aoki, 2000), sandcastles, or any other source of variation from a planar slope . Overall, the Werner and Fink (1993) model remains a landmark study because it introduced the idea of selforganization to explain the occurrence of morphological patterns, emphasized the role of morphodynamics, and paved the way to many new studies on the role of selforganization in the nearshore.…”
Section: Discussion Of Beach Cuspsmentioning
confidence: 99%
“…Some possible causes might include groundwater effects, nonuniform, energetic uprushes, alongshore variations in grain size or even edge waves. It has been shown that the presence of large perturbations on a beach can trigger beach cusp formation [ Sunamura and Aoki , 2000], but the minimum size of such perturbations required to initiate beach cusp morphology is unclear. It is therefore still possible that standing edge waves of undetectable (by this set of measurements) amplitude could have initiated beach cusp formation, however, these edge waves would clearly not have been energetic enough to dominate the wave field as previously hypothesized.…”
Section: Discussionmentioning
confidence: 99%
“…A recent field experiment by Sunamura and Aoki (2000), who used a suspended video-camera system to monitor continuously the process of cusp development from a manually flattened, plane section of a coarse clastic beach, indicated that cusps gradually and successively grew up along the beach section under the action of waves normal to the beach. A similar alongshore growth of beach cusps has been observed in a wave basin experiment in which a planar model beach was exposed to normally incident waves.…”
Section: Introductionmentioning
confidence: 99%
“…This flow pattern, called dhorn-divergent flowT by Masselink and Pattiaratchi (1998), is similar to the one already reported from the cusp field at various places (e.g., Bagnold, 1940;Sallenger, 1979;Pyökäri, 1982;Dean and Maurmeyer, 1980;Holland and Holman, 1996;Masselink et al, 1997;Sunamura and Aoki, 2000), and is probably instrumental in maintaining cusp configurations (Masselink and Pattiaratchi, 1998). It is evident that horn-deflected swash pattern plays a crucial role in determining the spacing of beach cusps.…”
Section: Introductionmentioning
confidence: 99%